Original burger (traditional) or burger with mushroom addition? A social representation approach to novel foods - Patinho I. (2021)
The authors are grateful to CAPES (Coordena??o de Aperfei?oamento de Pessoal de N?vel Superior, Brazil). IP received the M.Sc. scholarship of the CAPES (n? 1766129). JD Rios-Mera thanks the support of the Consejo Nacional de Ciencia, Tecnolog?a e Innovaci?n Tecnol?gica - CONCYTEC from Peru (CIENCIACTIVA programme, PhD scholarship contract: No. 238-2018-FONDECYT). The authors would also like to thank Zucca mushrooms Company, VPJ Foods, Ibrac Additives and Condiments and Sealed Air Brazil, for donating ingredients, raw materials and packaging. IP is supported by doctoral fellowship from the FAPESP (Process N? 19/26026-2). CJCC is supported by a grant from FAPESP (Thematic Project N? 17/26667-2).